PERAN KEPALA SEKOLAH SEBAGAI PEMIMPIN PEMBELAJARAN DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMP N 2 TAMAN - Urip Suwarniti; Mustaidah, Mustaidah; Shofa Fuadi; Ngurah Ayu Nyoman M (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of study to analyze the role of the principal as a learning leader in improving the quality of education at SMP Negeri 2 Taman, Pemalang Regency. The research method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the role of the principal as a learning leader in improving the quality of education at SMP Negeri 2 Taman, Pemalang Regency, has been implemented effectively. In terms of the role of the principal as a learning leader, it is reflected in his ability to formulate a clear learning vision. In terms of the principal's strategy in leading learning, it is reflected in the ongoing professional development of teachers. The challenges faced by the principal in carrying out his role as a learning leader include limited resources, resistance to change, and administrative workload. Meanwhile, the impact of the principal's leadership on the quality of education at SMP Negeri 2 Taman is an increase in student learning outcomes.